Percutaneous stent implantation for occluded central shunts in adults: A case report and review of current evidence - Jenab, Yaser; Rezaee, Malihe; Hosseini, Kaveh; Ghaderian, Homa; Haddad, Raymond N.; Zaidi, Ali N. (Frontiers in Cardiovascular Medicine, 2022)
Background: Patients with cyanotic complex congenital heart defects (CHDs) commonly undergo palliation with interposition of systemic-to-pulmonary shunts (SPSs). These palliative shunts are rarely found in adults with CHDs and can be complicated with progressive obstruction or total occlusion during follow-up. The best treatment option for shunt re-permeabilization is challenging and case-oriented because most patients are high risk candidates for redo surgeries. We aim to review the current evidence on percutaneous stent implantation to treat failed SPSs. Method: We performed a comprehensive literature review on percutaneous stent implantation to treat failed and occluded SPSs. We also reported the case of a 33-year-old man with cyanotic CHD and an occluded central aorto-pulmonary shunt, who was successfully treated with percutaneous balloon dilatation and subsequently stent implantation at our institution. Result: We identified and included 31 articles reporting on 150 patients and 165 stent implantations in failed SPSs. The age of patients at the time of stent implantation ranged from 6 days to 47 years. The time between the surgical shunt creation and transcatheter intervention ranged from 1 day to 17 years. Overall, 161/165 (97.5%) stent implantations were successful. The most common clinical presentation was cyanosis and decreased atrial oxygen saturations and the indication for stent implantation was shunt obstruction and stenosis. Conclusion: This review highlights the benefits of endovascular stenting to permeabilize failed SPSs in children and adults with complex CHD who are classified as poor candidates for re-surgical repair.